Economic Inequality in the Arab Region - Hassine, Nadia Belhaj (World Bank, Washington, DC, 2014)
The paper uses harmonized household survey micro-data to assess the levels and determinants of economic inequality in 12 Arab countries. It focuses on the sources of rural-urban, as well as metropolitan-nonmetropolitan, inequalities and applies the unconditional quantile regression decomposition technique to analyze the welfare gaps across the entire distribution. The analysis finds moderate inequality levels, with the Gini coefficient for the distribution of household real per capita total expenditures ranging between 30.7 in Libya and 45 in Mauritania. Differences in households' endowments, such as demographic composition, human capital, and community characteristics, appear as the main sources of the urban-rural welfare gap. There is inequality between metropolitan and non-metropolitan regions in many countries, mainly because of differences in returns to households' characteristics and particularly returns to human capital.